Análise da relação entre auditoria, governança e desempenho financeiro - Naiara Leite dos Santos Sant' Ana (2019)
In this thesis, the general objective was to analyze the relationship between independent auditing, corporate governance and financial performance. The specific objectives were: i) to analyze the characteristics of the Ibovespa companies, considering the size of the audit firm that audits them, the content of the audit reports, as well as the companies performance for the years 2010 to 2017; ii) to estimate an audit quality index - IQUA 2019 of the Ibovespa companies, for the years 2010 to 2017; iii) to create an Index of economic performance of Ibovespa companies for the years 2010 to 2017 and segregate economic efficiency by the size of the audit firm; iv) to construct a corporate governance index - IGC 2019 of the Ibovespa companies for the years 2010 to 2017 and to analyze the relationship between this and the companies' market value. The sample consisted of 26 companies. Procedures and methodological techniques used: i) content analysis, calculation of ROA, ROE, EBITDA/PL, EBITDA/TA, financial leverage, QTOBIN and EV/EBIT, average test; ii) calculation of conservatism using the Basu model (1997) and regression analysis with panel data, estimated using the generalized moments method; iii) calculation of the indicators of profitability and market value, correlation test and analysis by data envelopment; iv) principal components analysis, Granger causality and QTOBIN calculation. The main results were: i) 95.19% of the audits were performed by Big Four, 166 emphasis paragraphs were observed, 107 other subjects, 187 main audit subjects, 52 other information, 49 auditor responsibility and 52 management responsibility; the three most leveraged companies were Cia Siderúrgica, Braskem and Lojas Americanas and, consequently, they were the ones with the highest audit quality. About Delay JBS was the company with the worst audit quality, while Fibria achieved the best result. On average, there were differences in the performance of companies audited by Big Four and not Big Four (QTOBIN) and Big Four, PricewaterhouseCoopers and Deloitte, for QTOBIN, ROA, EBITDA / PL and ROE; and Ernst & Young and KPMG for QTOBIN and ROE; ii) the greater the size of the firm, the time of auditor-client relationship, the specialization of the audit firm, the financial leverage of the client company, the fees and the precaution with which positive news is accounted for, in detriment of bad ones, greater the audit quality; iii) in all indicators, the performance of the companies audited by Big Four was higher than the others. Companies audited by Deloitte have higher financial performance; the companies audited by the large audit firms have economic efficiency superior to those audited by the other audit firms; iv) the quality dimension of the audit is the one that is most relevant to the best practices of corporate governance, with 30.87%, followed by protection to minority shareholders, with 20.33%; compensation to managers, 16.65%; ownership and control structure, 13.99%; composition of the board of directors, 10.15% and, Transparency, 8.01%. Corporate governance has an effect on the market value of companies.